STRATEGI MENINGKATKAN OUTCOMES PASCA PELATIHAN VOKASI TUKANG BAHAN BANGUNAN PAVING BLOK PROGRAM KOTAKU - Lily Rahmawati Harahap; Ellys Thoyib; R Y Effendi; Rahmi Aryanti (MBIA, 2021)
This study aims to analyze how much change is experienced by vocational training participants in paving block construction materials on learning in attitudes, knowledge, general skills, and specific skills (outcomes). In addition, this analysis is also intended to determine how the effect of vocational training on paving block construction materials on the results of the changes obtained. The training was held on December 21-24, 2020, at the Faculty of Engineering, University of IBA Palembang. Forty participants attended the training. The data in this analysis were obtained through pre-test and post-test. These changes are described in 4 predicates using simple regression analysis: excellent, better, already good, and not good. The regression results showed that an average of 15.625% of the participants experienced an increase in results, an average of 76.25% of the participants obtained stable/stable results, and an average of 8.125%. Of the participants experienced a decrease in results. The analysis results found that training had an effect of 3.1% on participants' attitudes, 15.8% on participants' knowledge, 19.8% on general skills of participants, and 0.2% on specific skills of participants. The R-square value is not very influential because most of the participants are craftsmen who have experience making paving blocks. It takes a strategy of activities focused on goals and an activity strategy to improve the final result. Thus, the participants' primary objective is to become competent construction workers of infrastructure, road construction, and settlements construction infrastructure can be achieved. Keywords: vocational training, attitude change, knowledge, general skills and special skills Abstrak Penelitian bertujuan memberikan solusi atas capaian pembelajaran (outcome) yang dicapai peserta setelah pelatihan vokasi tukang bahan bangunan paving blok. Pelatihan dilaksanakan 21-24 Desember 2020 di Fakultas Teknik Universitas IBA Palembang. Peserta berjumlah 40 orang, dan semuanya menjadi responden. Jawaban pre-test dan post-test, menunjukkan ada perubahan jumlah peserta terhadap capaian pembelajaran yaitu ; sikap, pengetahuan, keterampilan umum dan keterampilan khusus. Peserta dengan outcome meningkat 15,625%, yang tetap/stabil 76,25% dan peserta dengan outcome menurun 8,125%. Jawaban tersebut diregresi juga untuk mengetahui pengaruh pelatihan terhadap perubahan sikap, pengetahuan, keterampilan umum dan khusus. Hasilnya menunjukkan ada perubahan sikap sebesar 3,1%, pengetahuan 15,8%, keterampilan umum 19,8% dan keterampilan khusus 0,2%. Pengaruh (R square) memang tidak begitu besar, namun begitu jelas bahwa pelatihan vokasi ada pengaruh terhadap outcome peserta. Dibutuhkan strategi aktifitas terarah ke tujuan (goal directed activity) dan strategi aktifitas tujuan (goal activity) untuk meningkatkan outcome peserta pasca pelatihan, sehingga tujuan menjadi tukang bahan bangunan untuk infrastruktur pembangunan jalan dan permukiman yang kompeten dapat tercapai. Kata Kunci: pelatihan vokasi, perubahan sikap, pengetahuan,keterampilan umum dan keterampilan khusus